Microstructure of the otoliths of the glacier lanternfish, Benthosema glaciale - García Seoane, Eva; Meneses, I.; Silva, A. (Marine and Freshwater Research, 2014)
8 pages Ageing using otolith microstructure is based on the assumption that growth increments are deposited daily. Individuals of the glacier lanternfish (Benthosema glaciale) were collected in the Flemish Cap (north-west Atlantic) during June–July 2010. A total of 44 individuals (ranging from 28 to 49 mm standard length; <2 years old) were selected to analyse otolith microstructure using light microscopy in order to assess the reliability of the use of microincrements to infer the true age of this species. Three distinct zones were distinguished: the larval zone, the postlarval zone and the postmetamorphic zone. The otolith core was, on average, 8 ± 0.7 μm. The mean microincrement number in the larval zone was 42 ± 7.5 within a radius of 0.095 ± 0.010 mm whereas in the postlarval zone it was 25 ± 3.0 within a segment of 0.104 ± 0.015 mm. SEM examinations in a subsample of otoliths showed that the resolution power of the light microscope was sufficient to study both the larval and the postlarval zones. Back-calculation from the time of capture suggests a hatching period from mid-June to mid-December with a peak in September. The spawning time and daily deposition of the microincrements in B. glaciale are discussed. Peer reviewed